Niche-specific functional heterogeneity of intestinal resident macrophages. Issue 7 (31st December 2020) - Viola, Maria Francesca; Boeckxstaens, Guy
Abstract : Intestinal resident macrophages are at the front line of host defence at the mucosal barrier within the gastrointestinal tract and have long been known to play a crucial role in the response to food antigens and bacteria that are able to penetrate the mucosal barrier. However, recent advances in single-cell RNA sequencing technology have revealed that resident macrophages throughout the gut are functionally specialised to carry out specific roles in the niche they occupy, leading to an unprecedented understanding of the heterogeneity and potential biological functions of these cells. This review aims to integrate these novel findings with long-standing knowledge, to provide an updated overview on our understanding of macrophage function in the gastrointestinal tract and to speculate on the role of specialised subsets in the context of homoeostasis and disease.